Material Requirement Planning (MRP) For Optimizing Raw Material Inventory in Cigarette Manufacturing - Pratama, Muhammad Fawwaz; Waluyowati, Nur Prima (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Improving inventory management capabilities is essential to enhance a company competitive advantage, especially in industries heavily reliant on raw materials. This study aims to implement the Material Requirement Planning (MRP) method to manage raw material inventory for cigarette production by identifying the most efficient lot sizing technique, determining optimal inventory quantities, and developing a procurement plan. This is a quantitative descriptive study using demand data, raw material composition, production sequences, schedules, and inventory records for Cakra Kretek Emas 16 at PT Cakra Guna Cipta. Data were collected through interviews and document analysis, then processed using forecasting, lot sizing, and MRP techniques. The results show inventory costs are Rp 52,042,771.2 with Economic Order Quantity (EOQ), Rp 41,707,679.53 with Part Period Balancing (PPB), and Rp 30,019,632.81 while use Wagner-Whitin Algorithm (WWA), Lot for Lot (LFL), and Period Order Quantity (POQ). This study applies POQ technique, which uses time intervals as the basis for placing orders. The novelty lies in the comparative analysis of multiple lot sizing techniques within an MRP framework in the cigarette industry. The application of MRP with POQ technique is expected to optimize and minimize inventory costs by reducing long-term storage through interval-based ordering.